Efficacy of progressive muscle relaxation intervention in mitigating compassion fatigue symptoms among nursing supervisors in hospital settings - Tri Ismu Pujiyanto (Physical Therapy Journal of Indonesia, 2026)
Background: Healthcare professionals, particularly nursing supervisors, face significant occupational wellness challenges related to compassion fatigue - a condition arising from prolonged exposure to patient suffering and administrative stressors. This investigation examined the therapeutic benefits of progressive muscle relaxation techniques in addressing compassion fatigue among nursing supervisors within hospital environments. Methods: A quasi-experimental study design incorporating pre-post assessment with control comparison was implemented. Thirty nursing supervisors from a general hospital participated through purposive selection, randomly allocated to treatment (n=15) and comparison groups (n=15). The treatment cohort received eight structured progressive muscle relaxation sessions across four weeks. Compassion fatigue assessment utilized the professional quality of life scale (ProQOL) version 5. Statistical evaluation employed paired and independent t-test analyses. Results: Treatment group participants demonstrated substantial compassion fatigue score reductions from 28.7±4.2 to 19.5±3.9 (p<0.001), whereas comparison group scores remained unchanged (p=0.082). Post-treatment between-group analysis revealed significant differences (p<0.001). Physical manifestation improvements included notable reductions in muscular tension and fatigue symptoms. Conclusion: Progressive muscle relaxation intervention effectively diminished compassion fatigue levels and associated somatic symptoms among nursing supervisors. This approach represents a practical, evidence-based, non-pharmacological strategy for addressing occupational health challenges in healthcare settings.